Evaluation of brushless DC motor structure design for the electric impact using 3-D finite element analysis - M. Senthil Raja; B. Geethalakshmi (International Journal of Applied Power Engineering (IJAPE), 2022)
In this article, an analytical model is deployed to optimize and design an interior permanent magnet brushless DC motor (IPMBLDC motor) when compared to theoretical structure of IPMBLDC. In this motor, assume air-gap of magnet assembly, distribution of flux density coefficient, selection of functional point in the permanent magnet, Torque density, and permanent magnet dimension compares with air-gap were deployed in an ideal design model. An equivalent circuit of magnetic field was improved and compare with the total flux density distribution and the torque density efficiency is based on initial ideal design factors. In finite element of MAXWELL 3D method, an electromagnetic field is investigated and used to verify an advanced equivalent circuit of magnetic field and improve the IPMBLDC motor factors. Finally, simulation results of IPMBLDC motor are verify and compare with ideal factors of IPMBLDC motor.